Evaluation of Drug Prescribing Pattern in Government-Owned Secondary Healthcare Facilities in South-West Nigeria - Adeola Adebisi Michael; Omole Moses Kayode; Itiola Oludele Adelanwa; Awoyomi Olajoju Jokotola (African Journal of Clinical Medicine and Pharmacy Research, 2026)
Rational prescribing is essential for achieving optimal therapeutic outcomes, whereas irrational prescribing may compromise patient safety and treatment effectiveness. Evidence regarding prescribing practices in accordance with the World Health Organization and International Network for Rational Use of Drugs (WHO/INRUD) recommendations remains limited in government-owned secondary healthcare facilities in Ogun State. This study examined drug-prescribing patterns in three secondary healthcare facilities and evaluated their conformity with the WHO/INRUD core drug-use indicators. A retrospective review was conducted using 3,000 prescriptions, with 1,000 prescriptions assessed at each facility. Of the patients represented in the reviewed prescriptions, 1,143 (38.1%) were male, and the mean age was 41.22 ± 19.13 years. The average number of medicines prescribed per encounter was 3.0 ± 1.7. The percentage of medicines prescribed by generic name was 59.2 ± 33.8%, whereas the percentage of encounters involving an antibiotic was 47.9 ± 26.9%. Furthermore, 83.7 ± 26.9% of the prescribed medicines were included in the Essential Medicines List. Nearly all assessed indicators deviated from the recommended WHO/INRUD values, demonstrating irrational prescribing practices across the three facilities. These findings highlight the need for regular and targeted training of prescribers to improve adherence to rational prescribing standards, promote safer medicine use, and enhance healthcare outcomes in secondary healthcare facilities.